QUANTITATIVE TEMPLATE FOR SUBTYPING PRIMARY PROGRESSIVE APHASIA - Mesulam, Marsel (2009)
OBJECTIVE: To provide a quantitative algorithm for classifying primary progressive aphasia (PPA) into agrammatic (PPA-G), semantic (PPA-S) and logopenic (PPA-L) variants, each of which is known to have a different probability of association with Alzheimer’s disease (AD) versus frontotemporal lobar degeneration (FTLD). DESIGN: Prospectively and consecutively enrolled 16 PPA patients tested with neuropsychological instruments and magnetic resonance imaging (MRI). SETTING: University medical center. PARTICIPANTS: PPA patients recruited nationally in the USA as part of a longitudinal study. RESULTS: A two-dimensional template, reflecting performance on tests of syntax (Northwestern Anagram Test) and lexical semantics (Peabody Picture Vocabulary Test), classified all 16 patients in concordance with a clinical diagnosis that had been made prior to the administration of the quantitative tests. All three subtypes had distinctly asymmetrical atrophy of the left perisylvian language network. Each subtype also had distinctive peak atrophy sites. Only PPA-G had peak atrophy in the IFG (Broca’s area), only PPA-S had peak atrophy in the anterior temporal lobe, and only PPA-L had peak atrophy in area 37. CONCLUSIONS: Once an accurate root diagnosis of PPA is made, subtyping can be quantitatively guided using a two-dimensional template based on orthogonal tasks of grammatical competence and word comprehension. Although the choice of tasks and precise cut-off levels may evolve in time, this set of 16 patients demonstrates the feasibility of using a simple algorithm for clinico-anatomical classification in PPA. Prospective studies will show whether this suptyping can improve the clinical prediction of underlying neuropathology.